2015
DOI: 10.4103/2229-5070.149924
|View full text |Cite
|
Sign up to set email alerts
|

Vulval myiasis: An unusual presentation of a rare entity in an adolescent female

Abstract: Human myiasis refers to parasitic infestation of body tissues by larvae of several fly species. The entity has a simple management. Human myiasis is well-documented in the literature however genital myiasis in females is scarcely reported in the literature. We hereby report this entity in an adolescent female who presented with urinary retention and concomitant urinary tract infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 7 publications
0
1
0
2
Order By: Relevance
“…in their study have reported a similar condition in a middle-aged female with mental ill health [3]. Vulval myiasis has also been reported in the literature [6]. Baidya et al.…”
Section: Discussionmentioning
confidence: 61%
“…in their study have reported a similar condition in a middle-aged female with mental ill health [3]. Vulval myiasis has also been reported in the literature [6]. Baidya et al.…”
Section: Discussionmentioning
confidence: 61%
“…La miasis urogenital humana puede ser externa o interna (2,9). La miasis externa es más frecuente en mujeres.…”
Section: Discussionunclassified
“…con nivel socioeconómico bajo que residen en regiones tropicales, subtropicales y templadas cálidas. Las larvas se alimentan de los tejidos del huésped, sustancias corporales líquidas o alimentos ingeridos (2)(3)(4).…”
unclassified